2020
DOI: 10.3390/medicina56090428
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Doppler Ultrasonography for First Trimester Prediction of Preeclampsia in Individuals at Risk from Low-Resource Settings

Abstract: Background and objectives: The objective of this study was to evaluate the potential of first trimester uterine artery Doppler ultrasonography for the early prediction of preeclampsia (PE), in at-risk pregnant women. Materials and Methods: This was a prospective longitudinal study, including 120 Caucasian pregnant women with risk factors for PE. The potential of pulsatility indexes (PI) and notch was assessed as a tool for preeclampsia screening. Results: Doppler examination of the uterine artery performed ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
3
11
2
Order By: Relevance
“…The data obtained in this study also showed that in PE screening, in patients at high risk, Doppler examination of the uterine artery performed early at 12-13 weeks allows the detection of pregnancies that will develop PE with a sensitivity of 75% and a specificity of 79% based on PI analysis. The results of our study are in agreement with other studies which, analyzing Doppler changes in the first trimester of pregnancy, reported similar detection rates of overall PE, with a higher prediction for early onset PE (<34 weeks) (18,24,25) . The present study showed that the best cutoff value of uterine artery PI for the prediction of early onset preeclampsia was ≥ 2.03 with accuracy of 79% and AUC of 76%.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The data obtained in this study also showed that in PE screening, in patients at high risk, Doppler examination of the uterine artery performed early at 12-13 weeks allows the detection of pregnancies that will develop PE with a sensitivity of 75% and a specificity of 79% based on PI analysis. The results of our study are in agreement with other studies which, analyzing Doppler changes in the first trimester of pregnancy, reported similar detection rates of overall PE, with a higher prediction for early onset PE (<34 weeks) (18,24,25) . The present study showed that the best cutoff value of uterine artery PI for the prediction of early onset preeclampsia was ≥ 2.03 with accuracy of 79% and AUC of 76%.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in consistency with the findings of Spencer et al (26) and Plasencia et al (23) , in which the uterine artery mean PI in the second trimester correctly predicts about 79% and 67% of all cases of PE. These values were slightly lower than what was documented by Adekanmi et al (11) , and higher than that documented by Oancea et al (18) , they reported AUC values of 86.2% and 62.12%, respectively. In the study of Yıldırım et al (12) , a comparable cutoff value was determined.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…According to this article ( 55 ), UAD at 11–14 weeks can confirm most pregnant women who will have PE and/or FGR. A prospective research involved 120 Caucasian pregnant women with high-risk factors for PE at 11–14 gestational weeks ( 70 ). Accordingly, the predictive sensitivity of UtA-PI for PE was 61.5, and the specificity was 63.8% ( 70 ).…”
Section: Uad and Pe/fgrmentioning
confidence: 99%